2013
DOI: 10.1002/humu.22302
|View full text |Cite
|
Sign up to set email alerts
|

Allele-Specific Expression at theRETLocus in Blood and Gut Tissue of Individuals Carrying Risk Alleles for Hirschsprung Disease

Abstract: RET common variants are associated with Hirschsprung disease (HSCR; colon aganglionosis), a congenital defect of the enteric nervous system. We analyzed a well-known HSCR-associated RET haplotype that encompasses linked alleles in coding and noncoding/regulatory sequences. This risk haplotype correlates with reduced level of RET expression when compared with the wild-type counterpart. As allele-specific expression (ASE) contributes to phenotypic variability in health and disease, we investigated whether RET AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(42 reference statements)
2
3
0
Order By: Relevance
“…Moreover, we found that RET expression in cells either treated or not with GDNF does not correlate with any particular RET genotype, including the SNP tagging the predisposing RET haplotype (SNP2). The absence of undescribed variants lying in putative regulatory regions has also confirmed recent findings which suggest different tissue and time specific regulations of RET in adult and embryo (Matera et al, ). Similar negative results were also obtained when we attempted to draw a correlation between RET expression and gender.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Moreover, we found that RET expression in cells either treated or not with GDNF does not correlate with any particular RET genotype, including the SNP tagging the predisposing RET haplotype (SNP2). The absence of undescribed variants lying in putative regulatory regions has also confirmed recent findings which suggest different tissue and time specific regulations of RET in adult and embryo (Matera et al, ). Similar negative results were also obtained when we attempted to draw a correlation between RET expression and gender.…”
Section: Discussionsupporting
confidence: 78%
“…As shown in Figure , RET shows different mRNA levels in the PBMCs of two unrelated healthy donors (namely PBMC1 and PBMC2), a finding consistent with the amount of RET receptors we detected, as already reported (Rusmini et al, ), on the surface of the same PBMCs (data not shown). Previous observations regarding the high variability of RET receptor expressed on immune circulating cells are therefore confirmed (Matera et al, ; Rusmini et al, ). In addition, we also failed to explain the variable RET expression, as assessed by measuring mRNA and protein levels, in terms of both sex and age differences among donors' PBMCs (data not shown).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Single-nucleotide primer extension was performed using a specific kit (SNaPshot Multiplex Sistem, Thermo Fisher ® ) and oligos suitable for the mutation site (p.R79C) on both strand (forward primer: 5′-GAG​ATG​ATG​GAG​CTC​AAT​GAC​C-3; reverse primer: 5′-CTT​CTC​GAT​GTA​GCT​GGC​AAA​G-3′), followed by capillary electrophoresis on automated DNA sequencer (ABI PRISM ® 3130XL), according to a protocol already reported ( Matera et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…The PCR product of exon 1 was cloned using the genomic DNA of ID#110M subject as a template, into the TOPO TA vector (Invitrogen, Carlsbad, CA, USA) following the manufacturer’s instructions. The plasmid DNA isolated from 51 clones was directly sequenced using the Sanger protocol, as already reported ( Matera et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%